2022
DOI: 10.1088/1755-1315/1060/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Fertilizers as a Novel Technique for Maximum Yield in Wheat Biofortification (Article Review)

Abstract: The major issues influencing human health in developing countries is the nutrient deficiency in different field crops. Several problems with the low efficiency of using the traditional chemical fertilizers by plants, despite there are more development in agricultural cultivation. Therefore, biofortification with nano-fertilizers and nano-biostimulants have been proposed as potential ways to enrich diets with nutrients. Organic fertilizers confront the issue of extending the duration of nutrient release and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 144 publications
0
13
0
Order By: Relevance
“…Earlier studies have assessed the method of applying NPs, such as through direct soil application [ 34 ], hydroponic [ 35 ], seed priming [ 36 ], and seed coating [ 37 ], and concluded that foliar application is most effective for plant growth and biofortification under both normal and abiotic stress conditions [ 26 , 38 ]. It has been noted that foliar application of NPs increased the concentration of the respective micronutrients in barley, rice and wheat, which led to an enhanced yield and quality [ 19 , 39 , 40 ]. Foliar-applied NPs enter the cells through the leaf through cuticle or stomata, and are then transported into the seeds through apoplastic and symplastic pathways, into the vascular system [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have assessed the method of applying NPs, such as through direct soil application [ 34 ], hydroponic [ 35 ], seed priming [ 36 ], and seed coating [ 37 ], and concluded that foliar application is most effective for plant growth and biofortification under both normal and abiotic stress conditions [ 26 , 38 ]. It has been noted that foliar application of NPs increased the concentration of the respective micronutrients in barley, rice and wheat, which led to an enhanced yield and quality [ 19 , 39 , 40 ]. Foliar-applied NPs enter the cells through the leaf through cuticle or stomata, and are then transported into the seeds through apoplastic and symplastic pathways, into the vascular system [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These achieved results show the high importance of applying these combined fertilizers by their role in affecting cell growth and division and thus affecting the yield [41]. Through the results showed about the increase in grain yield with the highest significant improvements obtained (5.891 Meg ha -1 ) in comparing with the plants of the comparison treatment, we can confirm the important role of Nano fertilizers as a promising technology for sustainable agriculture and environment, because it works in smaller quantities and the use of higher efficiency compared to traditional fertilizers with slow release, in addition to the smart targeting of the sites of absorption in the plant with a high speed in nutrient release, transport and representation within the plant, which enhances and promotes a high response for optimal growth and the good quality of yield [42][43][44]. Agricultural efficiency is based on the quantity and effect of the add-ons to the plant, so it's considered as an indicator of the efficiency of the materials used, and through the results of values achieving to the agricultural efficiency, we can observe the role and effect of Nano-fertilizers, so this signifies a novel approach towards the utilization of nanotechnology as opposed to the conventional means of fertilizer application and traditional fertilizers combinations with less efficient.…”
Section: Discussionmentioning
confidence: 72%
“…Nano fertilizers are considered a modern technology that has entered the agricultural scientific fields and the fertilizer industry, and play an effective role in improving the balance and rationing of the use of fertilizers, which contributes to improving food production and quality and reducing the resulting environmental pollution, especially for improved, high-quality varieties that are highly responsive to fertilizers [15], and nanometer-sized fertilizers have the ability to penetrate the plant body and improve the uptake efficiency of the roots and leaves (for foliar spray) [16], and improve the release of nutrients in a slow and balanced manner so that they are able to improve nutrients availability in the soil and the rhizosphere zone on a regular basis. Nano fertilizers are widely used for crops by foliar application of micro nutrients and bio stimulators, as this method is considered highly efficient in delivering the necessary nutrients into the plant body and reducing waste, and it is also considered a more effective method than application on the soil or to the root zone [17]. The use of nanoscale cerium oxide (CeO2) by foliar spraying of rice (Oryza sativa L.) can bring about important changes in the plant and increase the proportions of some nutrient compounds in rice grains, where the nanometer size of particles used as fertilizers plays a major role in the biological activity within the plant`s body, especially within the limits of (5 -100) nanometers, because it is absorbed, transported, and represented within the plant body with high efficiency, with nutrients released slowly and according to the plant's need [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to Table (4), the difference in the treatments did not achieve any significant difference between them in the quality of the harvest index.…”
Section: Harvest Index %mentioning
confidence: 94%